1999
DOI: 10.1063/1.124004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluorine dimer excimer laser radiation on the optical transmission and defect formation of various types of synthetic SiO2 glasses

Abstract: Changes in the optical absorption and the formation of point defects in three types of synthetic SiO2 glasses, wet (OH content; 120 ppm), dry (OH content <1 ppm), and fluorine (F)-doped (∼1 mol %) SiO2 glasses, by irradiation with fluorine dimer (F2) excimer laser light pulses (∼8 mJ/cm2/pulse×3.6×105 pulses) were examined by various spectroscopic methods. Intense optical absorptions were induced in the wet and dry silicas in the range of 4–8 eV, whereas the intensity of absorptions induced in the F-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 17 publications
(10 reference statements)
1
41
0
Order By: Relevance
“…The suggested mechanism of this phenomenon is the stabilization of radiation-created oxygen interstitials by transforming them to silanol bonds. A dramatic improvement of VUV transparency and excimer laser toughness takes place [65] in silica glass doped by fluorine (≈0.1-1 wt%). Fluorine is incorporated in silica mainly [66] in the form of SiF groups, which help to relax the silica network by building into the strained sites (Fig.…”
Section: Strained Bonds and Role Of Hydrogen And Fluorine Dopantsmentioning
confidence: 99%
“…The suggested mechanism of this phenomenon is the stabilization of radiation-created oxygen interstitials by transforming them to silanol bonds. A dramatic improvement of VUV transparency and excimer laser toughness takes place [65] in silica glass doped by fluorine (≈0.1-1 wt%). Fluorine is incorporated in silica mainly [66] in the form of SiF groups, which help to relax the silica network by building into the strained sites (Fig.…”
Section: Strained Bonds and Role Of Hydrogen And Fluorine Dopantsmentioning
confidence: 99%
“…In 1980s, such F-doping effects had attracted much attention for fiber applications. Then, it was also found that F-doping improves the resistance to vacuum-ultraviolet (UV) light (<200 nm) 21) and gammaray irradiation, 23)25) and silica glass became available as optical materials for vacuum-UV applications, as shown in Fig. 3.…”
Section: Fluorine Doping Of Silica Glass 21 Discovery Of Fluorine Domentioning
confidence: 99%
“…ppm F-doping. 49) Hosono et al 21) examined the radiation toughness of several silica glasses; F-doped silica glass, dry silica glass (the SiOH content <1 ppm), and wet silica glass (the SiOH content ³120 ppm). The concentration of the residual OH bond in the F-doped glass was close to that in the dry silica glass.…”
Section: Mechanism Of F-doping Effectmentioning
confidence: 99%
“…In general, such point defects result in undesirable degradation of electrical and/or optical properties, but they can also be used to exhibit some specific features or applications. A variety of metastable defects in glasses have been observed under an excimer laser and a femtosecond laser induces a variety of metastable defects [1][2][3]. It is hence likely that some novel optical functions can be elicited if the characteristics and quantities of the defects can be controlled.…”
Section: Introductionmentioning
confidence: 99%